Paths and Rivers; Sa'dan Toraja Society in Transformation - Waterson, Roxana (Verhandelingen van het Koninklijk Instituut voor Taal-, Land- en Volkenkunde, 2009)
Fieldwork extending over a thirty-year period provided materials for this book. Paths and Rivers offers an unusually deep and broad picture of the Sa'dan Toraja as a society in dynamic transition over the course of the past century. The Toraja inhabit the mountainous highlands of South Sulawesi, Indonesia, and are well known for their dramatic architecture, their unusual cliff burials, and their flamboyant ceremonial life, which places extraordinary economic demands on individuals and families. The analysis is informed, firstly, by a comparative perspective which sets Toraja social structure in the context of the Austronesian world. Secondly, the author delves deeply into Toraja social memory to show how people think about the past. She examines the usefulness of history and myth in the present as a source of identity, a template for action, or a resource by means of which to claim precedence. The book gives a clear picture of the structure and ethos of the indigenous Toraja religion, the Aluk To Dolo or 'Way of the Ancestors', with its complex cycle of rituals. The book concludes with an analysis of the ceremonial economy, which draws upon both domestic subsistence production and the global market economy. Paths and Rivers draws together a fascinating picture of one society's journey into modernity. Roxana Waterson is Associate Professor in the Department of Sociology, National University of Singapore. She is also the author of The living house: an anthropology of architecture in Southeast Asia (3rd ed., Thames and Hudson, 1997) and Southeast Asian lives: Personal narratives and historical experience (Singapore University Press/Ohio University Press, 2007).